Giant congenital melanocytic nevus of the scalp: from clinical-histological to molecular diagnosis - Yi Sun; Yun Zou; Lizhen Wang; Hao Gu; Qingqing Cen; Hui Chen; Xiaoxi Lin; Ren Cai (Hereditas, 2020)
Abstract Congenital melanocytic nevus (CMN) is a benign proliferative skin disease in the epidermis and dermis. Large to giant CMNs are estimated to be associated with an increased lifetime risk of malignancy. It is necessary to estimate and monitor the risk of malignant transformation for giant CMNs. To date, the clinical “ABCD” criteria and immunohistochemistry studies can be confusing and, to some extent, subjective. Accordingly, the elucidation of genomic analyses of nevi is required to better understand the malignant transformation of CMNs. Here, we describe two large to giant CMNs of the scalp with opposite clinical-histological and molecular evaluations of potential malignancy risk. To our knowledge, this is the first description of a genetic study of large to giant CMNs of the scalp in East Asia. We recommend reviewing the molecular diagnosis together with careful medical history and histological information to facilitate the evaluation of the potential malignancy risk.